(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study aims to develop a Student Grade System that will promote awareness and transparency for the students, faculty, and school administrators to help improve the monitoring of the student’s academic performances. The modified waterfall approach was used in the design and development of the Grade Management System, utilizing a validated survey questionnaire to determine the end-user requirements for the system. The system also underwent a series of evaluations to check whether it adheres to software quality standards using the criteria set forth by McCalls. Likewise, a User Acceptance Testing (UAT) was conducted to determine the system’s acceptability based on the variables under study and the end-user requirements. There was an evident need to develop the student grade management system based on the data gathered from the three survey instruments. In the Planning phase, we reviewed the grading system carefully and considered how it can help teachers facilitate their student grading process. In the Analysis phase, the primary purpose of the grading system is to accurately, consistently, and fairly communicate learning progress and achievement to students, families, postsecondary institutions, and prospective employers. In the Design phase, the proposed Grading System will be secured and reliable in keeping the records. It will also minimize the workload and will be fast and convenient. In the Development Phase, the Digital portfolios are multimedia collections of student work. They showcase student learning and skills and allow teachers and students to curate students’ best work. (American University, n.d.) In the Testing phase, the Laboratory activities involve reasoning, teamwork, experimental design, data acquisition and recording, data analysis, discussion, interpretation, and reporting. This research focuses on developing and implementing an adaptive learning and grading system to increase the effectiveness and quality of feedback to students. By utilizing various concepts from established learning theories, this research aims to improve the quantity, quality, and speed of feedback as it pertains specifically to the grading of computer skills with a focus on personal productivity software.